Explaining communities' adaptation strategies for coastal flood risk: Vulnerability and institutional factors - Stephanie E. Chang; Jackie Z. K. Yip; Tugce Conger; Greg Oulahen; Emily Gray; Michelle Marteleira (Journal of Flood Risk Management, 2020)
Abstract Increasing coastal flood risk has prompted a proliferation of cities that are adopting risk reduction and adaptation tools. This article inquires into what types of tools local governments tend to adopt for managing coastal flood risk and the factors that may be influencing these choices; in particular, factors related to hazard vulnerability and institutional capacity. Focusing on 40 diverse coastal communities in a study region in Canada, the study utilised data from the communities' Official Community Plans to characterise their approaches to managing coastal flood risk in terms of land use regulations, construction specifications, and/or structural flood protection tools. The data revealed considerable diversity in the portfolio of tools that the communities have adopted. Tool adoption was found to correlate strongly with hazard vulnerability; that is, communities with similar physical and socio‐economic vulnerability conditions tended to take similar adaptation actions. For example, established communities with highly urbanised coastlines tended to rely on structural flood protection while suburban communities with semi‐developed coastlines predominantly utilised land use regulations. Institutional factors such as resource availability and local leadership, which were operationalised using survey data, exhibited surprisingly little correlation with the types of tools that communities adopted.